SCIENTIFIC-THEORETICAL FOUNDATIONS OF THE PROBLEM OF FUTURE ARABIC LANGUAGE TEACHER COMPETENCE (Academicia Globe: Inderscience Research, 2023)
The article examines the concept of competence and its historical penetration into education in three stages, the opinions of scientists attributed to the concept of competence, the term "competence", starting with the definition of linguistic identity, becoming an economic and managerial term and currently entering scientific circulation due to observation in all pedagogical processes, the need for learning Arabic requires a lot factors that intersect subjectivity and objectivity.